Hubungan Efikasi Diri Terhadap Kepatuhan Pembatasan Cairan Pada Pasien Penyakit Ginjal Kronik (Pgk) Yang Menjalani Hemodialisis Di Rsup Dr. M. Djamil Padang - Fitria Alisa; lola Despita sari; Lenni Sastra; Weny Amelia; Ria Desnita (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2022)
Patients with chronic kidney disease who do not adhere to fluid intake restrictions will experience a buildup of fluid causing lung edema and hypertrophy in the left ventricle. Fluid buildup in the body can cause severe heart and lung function, resulting in shortness and tiredness of the patient. The purpose of this study was to determine self-efficacy with adherence to fluid restriction in patients with chronic kidney disease (CKD) who underwent hemodialysis at RSUP Dr. M. Djamil Padang. This type of analytic research with cross sectional design. The research was analyzed univariately and bivariately using the Chi-Square test. The results showed that more than half of the respondents (51,8%) had non-adherent fluid restriction compliance. Less than half of the respondents (42.6%) had poor self-efficacy. There is a significant relationship between self-efficacy and adherence to fluid restriction in patients with chronic kidney disease undergoing hemodialysis (pvalue=0,025).